Critical Analysis of Blood Transfusion Safety: Coordination Between Nursing And Laboratory Professionals - Alshammari , Bassam Shyhan F; Alruwili , Wejdan Saqer S; alshammari , Khalda mnawer; Alshammari , Ayman Mojeda; Alshamrani , Sultan Ahmed; Alrowili , Taghreed Jazza; Alanazi , Abdulmajeed Obaidallah; Alrowili , Mohammed Dhaher; Alshamari , Ahmed Zahi F; Alsharari , Aqla Salem; Alsharari , Bassam Lahi; Alsharari , Saleh Mohammed; et al. (Journal of Ecohumanism, 2024)
Blood transfusion is one of the most important healthcare activities, and effective collaboration between the nursing and laboratory staff is essential. In this paper, the authors analyze the state of knowledge regarding the contribution of interdisciplinary cooperation in improving safety for transfusions and define directions for further research and practice. Therefore, this paper draws heavily from the available literature and uses primary data from healthcare organizations to stress the need to involve teamwork and protocol compliance and embrace new technologies. Findings show that simplifying the communication structure, strict training of employees, and proper monitoring systems minimize errors regarding blood transfusions. The findings in this paper offer practical solutions to ensuring the safety of blood transfusions concerning the involvement of allied health practitioners.